ncreasing the Understanding of Pecific Numbers in Mathematics Lessons at Elementary School in the Drawing of Simple Flat buildings - Yohanes Kristanto Widyawan Ohoiwutun (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The aim of this classroom action research is to improve the ability to recognize simple flat shapes according to their elements and properties in class IV students at SD N 1 Manjung, Ngawen District, Klaten Regency for the 2021/2022 academic year. This research is Classroom Action Research (PKP) which was carried out in order to fulfill one of the PKP tasks. The form of this research is classroom action research consisting of two cycles, each cycle consisting of four stages, namely planning, implementation, observation and reflection. The research subjects were fourth grade students at SD N 1 Manjung. Data collection techniques use observation, tests and non-tests. The data analysis technique uses descriptive analysis techniques which consist of two analysis components, namely comparative and qualitative. The results of this research are (1) there is an increase in students' understanding of fractions through the use of pictures of flat shapes compared to before in the initial test 48; then in the first cycle test60; to 80 in the second cycle, (2) there was an increase in the percentage of student learning completeness which in the initial test was only 30%; and in the first cycle test 50%; then in the second cycle it becomes 100%.